2013
DOI: 10.1111/bjh.12661
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of paroxysmal nocturnal haemoglobinuria clone presence in aplastic anaemia patients treated with combined immunosuppression: results of two‐centre prospective study

Abstract: SummaryParoxysmal nocturnal haemoglobinuria (PNH) clones are frequently detected in patients with aplastic anaemia (AA). To evaluate the prognostic role of PNH clone presence we conducted a prospective study in 125 AA patients treated with combined immunosuppressive therapy (IST). Seventyfour patients (59%) had a PNH clone (PNH+ patients) at diagnosis, with a median clone size of 0Á60% in granulocytes and 0Á15% in red blood cells. The response rate at 6 months was higher in PNH+ patients than that in PNH-patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 41 publications
4
60
0
10
Order By: Relevance
“…When the two predictive parameters of ARC and ALC were combined, patients with higher baseline ANC and ARC had a response rate 40 % higher than those with lower baseline ANC and ARC (83 vs 41 %, p < 0.0001). The utility of ARC in predicting IST outcomes has been confirmed in a proportion of reports, but not in others [12,[14][15][16][17]. Higher absolute neutrophil count (ANC) appears to be correlated with a better response rate of IST [15,18]; however, this result was not confirmed in Japanese and German children [12,19,20].…”
Section: Pre-treatment Peripheral Blood Countsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the two predictive parameters of ARC and ALC were combined, patients with higher baseline ANC and ARC had a response rate 40 % higher than those with lower baseline ANC and ARC (83 vs 41 %, p < 0.0001). The utility of ARC in predicting IST outcomes has been confirmed in a proportion of reports, but not in others [12,[14][15][16][17]. Higher absolute neutrophil count (ANC) appears to be correlated with a better response rate of IST [15,18]; however, this result was not confirmed in Japanese and German children [12,19,20].…”
Section: Pre-treatment Peripheral Blood Countsmentioning
confidence: 99%
“…High sensitive flow cytometry analysis has indicated that 20-70 % of pediatric AA patients possess minor PNH populations at the time of diagnosis [17,[28][29][30]. In several studies, investigators have attempted to reveal the clinical significance of such PNH-type cells in patients with bone marrow failure.…”
Section: Paroxysmal Nocturnal Hemoglobinuria (Pnh)mentioning
confidence: 99%
“…21 Several other variables such as PNH-type cells are also associated with response to ATG and/or cyclosporine. [22][23][24] Another potential marker of an immunemediated aetiology for bone marrow failure is the presence of leukocytes lacking HLA-A alleles (HLA-LLs). 25,26 These cells develop from HSPCs with copy number-neutral loss of heterozygosity of the HLA-class I allele(s) owing to 6pUPD (uni-parental disomy of the short arm of chromosome 6).…”
Section: Can We Develop a Therapy Strategy Based On Pathophysiology Rmentioning
confidence: 99%
“…Although each disease has a unique manifestation, the immune mechanisms shown in blue are shared by all four diseases. When a patient with BM failure possesses a marker of immune pathophysiology such as PNH-type cells [8] or HLA allele-lacking cells [9], the patient should be treated with immunosuppressive therapy, irrespective of the formal diagnosis.…”
Section: Practical Approach To Treatments Of Acquired Bm Failure Syndmentioning
confidence: 99%